Diseases of wild and cultured juvenile crustaceans: Insights from below the minimum landing size - Behringer, Donald C. (Journal of invertebrate pathology, 2012)
Juvenile crustaceans such as the Caribbean spiny lobster Panulirus argus are often disproportionately affected by pathogens and parasites. The pathogenic virus Panulirus argus Virus 1 (center TEM), fundamentally alters the ecology of juvenile lobsters and can cause up to 50% mortality in a localized area. [Display omitted] ► Crustaceans are exceptionally valuable fishery and aquaculture organisms. ► Many crustacean pathogens show an affinity for juveniles. ► Juveniles are often underrepresented in studies of crustacean diseases. ► Diseases can have strong effects on fisheries through ecological impacts. ► Stock assessments should incorporate more information on juveniles and disease. Decapod crustaceans (i.e., lobsters, crabs, and shrimps) are all subject to disease, both in the wild and in culture. No life stage appears to be immune to some form of pathogen or parasite. However, juveniles appear to be the targets of some of the most pervasive and consequential diseases. It is therefore surprising, given the enormous economic value of adult decapods, that we know so little about the effects of pathogens on their vulnerable life stage. Here I review the significant diseases reported for juvenile decapods that support fisheries and aquaculture, and highlight research that demonstrates the advantage of incorporating juveniles and ecology in studies of disease.